Experimental and Numerical Study of Behavior of Additively Manufactured 316L Steel Under Challenging Conditions - Lenka Kunčická; Radim Kocich; Marek Pagáč (Metals)
AISI 316L stainless steel, widely used in numerous industrial fields, can be fabricated by conventional methods, but also by additive manufacturing. As materials prepared by additive manufacturing typically feature various printing defects deteriorating their mechanical and utility properties, post-processing by plastic deformation is able to enhance their performance. The determination of optimized post-processing conditions can advantageously be performed by combining experimental work and numerical simulations using the finite element method. The presented research focuses on investigating the deformation behavior of AISI 316L stainless steel prepared by additive manufacturing under a variety of thermomechanical conditions (temperatures of 900–1250 °C, strain rates of 0.1–100 s−1). Together with the deformation behavior of the steel, the kinetics of the occurring softening processes is also discussed. The experimentally acquired data are further used for numerical simulations to predict the expected magnitudes of force and imposed strains during prospective post-processing. Observing the microstructures and mechanical properties reveals that the prospective post-processing of AISI 316L stainless steel, prepared by additive manufacturing, via plastic deformation is the most favorable when performed at the temperature of 900 °C and using high strain rates. The flow stress/microhardness generally increase at lower temperatures and higher strain rates, as a result of the development of a substructure. On the contrary, higher temperatures support the recrystallization of grains and their coarsening, which consequently decreases the mechanical properties.